Prevalence of Bottle‐Feeding Practice and Associated Factors Among Mothers of Children Under Five in the World, 2024: Systematic Review and Meta‐Analysis - Demis Getachew; Eyob Getachew; Amlaku Nigusie Yirsaw; Habtamu Semagne Ayele; Getnet Alemu Andargie; Abriham Adane Lakew; Abiyu Abadi Tareke; Negesse Shiferaw Zeru; Gebeyehu Lakew (Reproductive, Female and Child Health)
ABSTRACT Background Child‐feeding practices, particularly breastfeeding, significantly impact children's health and survival. However, bottle feeding, although historically practiced, presents numerous disadvantages affecting optimal child nutrition and health. Despite World Health Organisation and The United Nations Children's Fund recommendations against bottle feeding, it remains prevalent globally, affecting roughly 59% of infants worldwide and 85% in Australia by 5 months of age. Objective This study aims to assess the prevalence and determinants of bottle feeding among mothers of children under five globally. Methods This systematic review and meta‐analysis adhered to the Preferred Reporting Items for Systematic Review and Meta‐Analysis guidelines. We comprehensively searched electronic databases for English‐language articles published between 2014 and 2024. The quality of studies was assessed using the Joanna Briggs Institute critical appraisal checklist. Data were analysed in STATA version 17, including summary tables, narrative descriptions, forest plots, and statistical heterogeneity and publication bias assessment. Results The pooled prevalence of bottle feeding among mothers was 57%. Subgroup analysis revealed higher prevalence in larger sample sizes (> 2151) and lower prevalence in smaller ones. Factors significantly associated with bottle feeding included mode of delivery (OR = 1.953; 95%, CI: 1.272, 2.635), child hospitalisation (OR = 1.984, CI: 1.593, 2.376), mother's occupation (OR = 1.579; CI: 1.467, 1.690), post‐natal care (OR = 2.965; CI: (1.358, 4.571), age of children (OR = 2.836; CI: 1.895, 3.777), place of residence (OR = 1.423; CI: 0.994, 1.852), and mother's education (OR = 3.366, CI: 1.949, 4.783). Conclusion Efforts to promote optimal child‐feeding practices should address the identified determinants, emphasising the importance of breastfeeding and providing support to mothers, especially those facing challenges such as cesarean delivery, child hospitalisation, and maternal employment.